2016
DOI: 10.3389/fpsyg.2016.00287
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Symptoms and Post-traumatic Growth in 223 Childhood Cancer Survivors: Predictive Risk Factors

Abstract: With modern therapies and supportive care, survival rates of childhood cancer have increased considerably. However, there are long-term psychological sequelae of these treatments that may not manifest until pediatric survivors are into adulthood. The prevalence of post-traumatic stress disorder in young adult survivors of childhood cancer ranges from 6.2 to 22%; associated risk factors are young age at the assessment, female gender, low education level, and some disease-related factors. The aim of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 52 publications
3
44
0
Order By: Relevance
“…This result was further supported by regression analysis, where higher levels of PTG were connected to older age at the T2 assessment. However, Tremolada et al found an opposite relation between PTG and the age at diagnosis, with younger children reporting more PTG [35]. PTG further correlates with self-esteem and depressive symptoms and PTSS is associated with lower self-esteem and higher levels of negative emotionality and depressive symptoms, which corresponds to prior studies [13,29,30,31,32].…”
Section: Discussionsupporting
confidence: 70%
“…This result was further supported by regression analysis, where higher levels of PTG were connected to older age at the T2 assessment. However, Tremolada et al found an opposite relation between PTG and the age at diagnosis, with younger children reporting more PTG [35]. PTG further correlates with self-esteem and depressive symptoms and PTSS is associated with lower self-esteem and higher levels of negative emotionality and depressive symptoms, which corresponds to prior studies [13,29,30,31,32].…”
Section: Discussionsupporting
confidence: 70%
“…Following data extraction and preliminary analyses, an email was sent to the authors of all 23 studies requesting unreported Pearson correlations for the specific variables measured in each study. Three authors provided additional relevant data; one indicated that the data requested from 2 studies were in fact from the same dataset. The more recent study was excluded from the results.…”
Section: Resultsmentioning
confidence: 99%
“…The more recent study was excluded from the results. Therefore, 22 studies were eligible for inclusion in the review. Four articles were excluded because the reported data were not in a format that could be used to calculate an effect size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations